Determining the source of unusual xenon isotopes in samples. (June 2022) - Eslinger, Paul W.; Ely, James; Cooper, Matthew W.; Foxe, Michael; Hayes, James C.; Mayer, Michael F.; Panisko, Mark E.; Sarathi, Ramesh
Abstract: Three unusual radioactive isotopes of xenon— 125 Xe, 127 Xe, and 129m Xe—have been observed during testing of a new generation radioxenon measurement system at the manufacturing facility in Knoxville, Tennessee. These are possibly the first detections of these isotopes in environmental samples collected by automated radioxenon systems. Unfortunately, the new isotopes detected by the Xenon International sampler can interfere with quantification of the radioactive xenon isotopes used to monitor for nuclear explosions. Xenon International sampling data collected during February through September 2020 were combined with an atmospheric transport model to identify the possible release location. A source-location analyses using sample counts dominated by 125 Xe strongly supports the conclusion that the release point is near (within 20 km) the sampler location. Wind patterns are not consistent with releases coming from more distant nuclear power plants. The High Flux Isotope Reactor (HFIR) and the Spallation Neutron Source (SNS) at Oak Ridge National Laboratory are located in the region of most likely source locations. The source-location analysis cannot rule out either facility as a release location, and some of the samples may contain a combination of releases from both facilities. The source-location results using 125 Xe are not unexpected because Klingberg et al. (2013) previously published the production rate of radioactive xenon isotopes from neutron activation of stable xenon in the air at the HFIR. Up to 10 12 Bq of 125 Xe could be produced per operational day and other xenon isotopes would be produced in lesser quantities. Highlights: A new radioxenon sampler at Knoxville, Tennessee, USA, detected 125 Xe, 127 Xe, and 129m Xe. These isotopes have not been previously detected in automated radioxenon samplers. These isotopes could interfere with measurements taken for nuclear explosion monitoring. A source-location analysis supports a release point close (20 km) to the detector. Facilities at Oak Ridge National Laboratory are the most likely release source.